2002
DOI: 10.1103/physrevb.66.104528
|View full text |Cite
|
Sign up to set email alerts
|

Hall coefficient ofLa1.88yYySr

Abstract: The Hall coefficient in the low-temperature tetragonal phase and the mid-temperature orthorhombic phase of La1.88−yYySr0.12CuO4 (y = 0, 0.04) single crystals is measured under high magnetic fields up to 9 T in order to investigate the detailed behavior of the transport properties at low temperatures in the stripe phase. When the superconductivity is suppressed by high magnetic fields, the Hall coefficient has negative values in low temperatures, and the temperature region of the negative values spreads as incr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Without the yttrium in the crystal, R H of La 1.88 Sr 0.12 CuO 4 does not go negative for magnetic fields of 6 T or less, but it does go negative at T Ͻ 18 K for fields of 8 T and higher. 82 ͑Note that a negative R H was not observed in a study of LSCO films; 83 however, this may be due to the sensitivity of stripe correlations to strain effects.͒ The crossing of R H from positive to negative on cooling, as seen in crystals with known stripe order, has also been observed in underdoped YBa 2 Cu 3 O 6+x and YBa 2 Cu 4 O 8 samples that also exhibit quantum oscillations at sufficiently high magnetic fields. 84 [89][90][91] We note that it may also be important to take into account the unusual correlations in the stripe-ordered phase that we will discuss further on.…”
Section: G Specific Heatmentioning
confidence: 99%
“…Without the yttrium in the crystal, R H of La 1.88 Sr 0.12 CuO 4 does not go negative for magnetic fields of 6 T or less, but it does go negative at T Ͻ 18 K for fields of 8 T and higher. 82 ͑Note that a negative R H was not observed in a study of LSCO films; 83 however, this may be due to the sensitivity of stripe correlations to strain effects.͒ The crossing of R H from positive to negative on cooling, as seen in crystals with known stripe order, has also been observed in underdoped YBa 2 Cu 3 O 6+x and YBa 2 Cu 4 O 8 samples that also exhibit quantum oscillations at sufficiently high magnetic fields. 84 [89][90][91] We note that it may also be important to take into account the unusual correlations in the stripe-ordered phase that we will discuss further on.…”
Section: G Specific Heatmentioning
confidence: 99%
“…19,20 A change from positive to negative Hall and Seebeck coefficients in YBCO around this doping region led to the interpretation that the Fermi pocket must have electron like character. [21][22][23][24][25] Negative Seebeck and Hall coefficients are also observed in La 1.8−x Eu 0.2 Sr x CuO 4 and several other La-based cuprates 23,24,[26][27][28][29][30][31] that are known to exhibit charge and spin-stripe order [7][8][9][32][33][34][35][36][37][38][39][40][41][42][43] . This strongly suggested that charge and/or spin order may exist in YBCO as well.…”
Section: Introductionmentioning
confidence: 99%
“…[11]) and LSCO with x = 0.12 (Ref. [28]) where the spin stripe correlation is developed but the charge stripe order is not. Accordingly, it may be the case that R H becomes zero owing to the stabilization of the charge-spin stripe order at x = 1/8, while it becomes negative owing to the instability of the charge stripe order for x < 1/8.…”
mentioning
confidence: 99%